A comprehensive method for remote monitoring of the high-voltage insulators - A. V. Golenishchev-Kutuzov; V. A. Golenishchev-Kutuzov; D. A. Ivanov; G. D. Mardanov; R. A. Husnutdinov; I. A. Evdokimov (Известия высших учебных заведений: Проблемы энергетики)
With the help of the developed two-channel method for remote control of high-voltage insulators have been studied peculiarities of characteristics of partial discharges (PD) for determining a working condition of insulators under high voltage. Therefore, they have established diagnostic principles for the allocation of faulty insulators, as well as predictive signs of the future lifetime of healthy insulators.